KONSEP PENDIDIKAN MULTIKULTURAL DAN PENDIDIKAN INKLUSIF - Fauzan, Mohd; Rajab, Khairunnas (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this writing is to know the concept of multicultural education and inclusive education. This study uses the method of literature review. The results showed that: 1) The dimensions of Multicultural Education: content integration, the knowledge construction process, a pedagogy, prejudice reduction, 2) The Functions of Multicultural Education: giving a clear self-concept, helping to understand the experiences of ethnic and cultural groups in terms of history, helping to understand that conflicts between ideals and reality exist in every society, helping to develop decision making, social participation, and citizenship skills, recognizing diversity in language use. 3) Inclusive Education Foundation, 4) Philosophical Foundation: The Indonesian nation is a cultured nation with the national symbol Garuda Bird, a universal viewof human rights , 5) Juridical Basis: UUD 1945 (Amendment) Ps. 31, Law no. 23 of 2002 concerning Child Protection, Ps. 48, Law no. 20 of 2003 concerning the National Education System, 6) Empirical Basis: Declaration of Human Rights, 1948, Convention on the Rights of the Child, 1989, World Conference on Education for All, 1990, UN Resolution number 48/96 of 1993 To achieve the goal of multicultural education.